2011
DOI: 10.4081/reumatismo.2008.50
|View full text |Cite
|
Sign up to set email alerts
|

Alexithymia and immunoendocrine parameters in patients affected by systemic lupus erythematosus and rheumatoid arthritis

Abstract: INTRODUZIONEN ei pazienti affetti da una malattia autoimmune cronica, come il lupus eritematoso sistemico (LES) o l'artrite reumatoide (AR), le va- Reumatismo, 2008; 60(1):50-56 0,5 SUMMARYObjective: Aim of this study was to evaluate the prevalence of alexithymia in patients affected by SLE or RA and to investigate the correlation between alexithymia and immunoendocrine parameters (PRL, hGH,. Methods: Twenty-five patients (12 and 13 affected by SLE and RA, respectively) were enrolled into the study. The T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
13
0
2
Order By: Relevance
“…Alexythimia is characterized by difficulty in recognizing and identifying emotions, dysfunction in distinguishing emotions from somatosensory feelings and by a particular cognitive attitude to concrete experiences (46). Some studies on small cohorts have found a higher prevalence of alexythimia in patients with autoimmune diseases (RA, SLE) [46]. Recently, Van Leeuwen et al observed that patients with pSS not differ from controls in terms of the processing and regulation of emotions, but rather in terms of interpretation and expression of the same feelings in accordance with the definition of alexythimia [47].…”
Section: Discussionmentioning
confidence: 99%
“…Alexythimia is characterized by difficulty in recognizing and identifying emotions, dysfunction in distinguishing emotions from somatosensory feelings and by a particular cognitive attitude to concrete experiences (46). Some studies on small cohorts have found a higher prevalence of alexythimia in patients with autoimmune diseases (RA, SLE) [46]. Recently, Van Leeuwen et al observed that patients with pSS not differ from controls in terms of the processing and regulation of emotions, but rather in terms of interpretation and expression of the same feelings in accordance with the definition of alexythimia [47].…”
Section: Discussionmentioning
confidence: 99%
“…We further investigated the possible relation between alexithymia, inflammation and neuro-endocrine dysregulation, assessing serum levels of prolactin (PRL), human growth hormone (hGH), interleukin-6 (IL-6) and tumour necrosis factor alpha (TNF-alpha. In SLE patients with alexithymia we found hyper-expression of PRL compared to nonalexithymia ones, however, there were no difference in the expression of inflammatory markers [15].…”
Section: Alexithymia In Slementioning
confidence: 52%
“…5 Çalışmalarda aleksitimik iletişim biçiminin başlangıçta psikosomatik hastalıklara özgü olduğu belirtilmişse de, günümüzde yalnızca bu hastalıklarda değil sağlıklı bireylerde de görüldüğü vurgulanmaktadır. 4,[6][7][8][9][10][11] Aleksitiminin ortaya çıkmasında sosyokültürel, kalıtsal ve çevresel faktörlerin etkili olduğu belirtilmektedir. Sosyoekonomik gelir seviyesi düşük olanlarda, kadınlarda ve ilerleyen yaşlarda aleksitimi görülme sıklığı artmaktadır.…”
Section: Introductionunclassified